Stripper simulation for co2 removal from natural gas processing plant using amine absorption process - Fakhirah, Ahmad Basri (2014)
Natural gas is consisting of gaseous mixture or hydrocarbon components and mainly contains methane. The gas from reservoir might also contain contaminants (acid gas) such as nitrogen (N2), carbon dioxide (CO2) and sulphur compounds. The natural gas should be purified from these contaminants in order to avoid health risk, environment risk and establish the standard specifications of natural gas. In this work, chemical absorption will be used as the method to separate the contaminants especially CO2 from natural gas processing plant. Chemical absorption processes generally are characterized by highly heat of acid gas absorption and it is required a lot of heat for regeneration. Thus, amount of steam to supply to reboiler will increase as heat of regeneration increase thus increased production cost. The aim of this work is to improve the operation of stripper column to reduce heat of regeneration so that the removal of CO2 from natural gas using amine absorption will be improved. Aspen Plus simulator is used as a tool to develop the column model. Several process parameters such as concentration, pressure and temperature are varied to determine the optimum process operation at minimum heat of regeneration. Based on the result obtained; the suitable range for each process parameters; DEA concentration, reboiler temperature and stripper pressure is in between 25 wt% and 35 wt%, 118 oC and 121oC, 1.5 bar and 1.75 bar respectively